Flap Fixation in Endoscopic Dacryocystorhinostomy: A Comparative Study - Vikas Sikarwar; Sushil Ojha; Ankur Joshi; Amit Shah; Rameet Sandhu; Pankaj Gandhi (Journal of Pharmacy and Bioallied Sciences)
Background: The usual procedure for nasolacrimal duct obstruction is dacryocystorhinostomy (DCR). Flap-based DCR techniques lead to better surgical outcome provided flaps do not dislocate in the post-operative period. Objectives: This study was conducted to compare gelfoam with merocel tamponade for fixation of mucosal flaps in endoscopic DCR. Materials and Method: Merocel tamponade was used for fixation of flaps in 26 patients. Gelfoam was used in 26 patients, and surgical results were compared. Results: The surgical success rate was greater in merocel tamponade fixation with less complications. Conclusion: Merocel tamponade can be used successfully for mucosal flap fixation in endoscopic DCR for better surgical outcome.